1999
DOI: 10.1002/(sici)1521-3897(199911)341:8<773::aid-prac773>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

X-ray photoelectron spectroscopy investigation of the interaction of U(VI) and Fe(III) with natural humic acid in aqueous solutions

Abstract: 773The determination of radionuclide speciation and factors influencing radionuclide migration in the environment is an important task in current radioecological research. Humic substances are present throughout the environment and are the main organic component in natural waters. Uranium can form strong complexes with humic substances in natural waters leading to increased solubility of uranium and an enhancement of its mobility. As a result of forty years of uranium mining in the Ore Mountains (Erzgebirge) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…In the case of HEIDI, there is one less carboxylate group in the molecule and so chelation takes place primarily on the M(III) cation. We note that this also aligns with the related work by Teterin et al [11] . where the humic acid was found to preferentially bind to the Fe(III) cation over the U(VI) ion.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In the case of HEIDI, there is one less carboxylate group in the molecule and so chelation takes place primarily on the M(III) cation. We note that this also aligns with the related work by Teterin et al [11] . where the humic acid was found to preferentially bind to the Fe(III) cation over the U(VI) ion.…”
Section: Resultssupporting
confidence: 92%
“…Teterin et al. observed that Fe(III) will preferentially bind to humic acid over U(VI) and the reaction is heterogeneous, [11] which likely contributes to the variability observed by Kuo et al [8] . However, Dublet et al.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation